PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP STRATEGI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Margareth Tefbana, Adelce; Andia Dekrita, Yosefina; Yuneti, Katharina (Universitas Nusa Nipa Maumere, 2025)
This research aimen to examine the effect of firm size and profitability on tax avoidance strategies in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020-2024. The analytical method used was quantitative associative research, conducted to test causality and the influence of independent variables on the dependent variable, with IBM SSPS Statistics 26 as the analytical tool. The findings showed that firm size had a positive and significant effect on tax avoidance, and similarly, profitability was proven to have a positive and significant effect on tax avoidance. Simultaneously, both independent variables affected tax avoidance, with a significance value of 0,002 < 0,05. The Adjusted R2 value of 0,32 indicated that 3,2% of the variation in tax avoidance was explained by firm size and profitability, while the remaining 96,8% was influenced by other factors outside the research model. Based on this findings, it was recommended that manufacturing companies, particulary large firms with high profitability, should continue to implement tax efficiency strategies in accordance with statutory regulations (legal tax planning).